Building the Bridge between Higher Learning Institution and Social Media Technologies through Mobile Learning in Malaysia - Ramakrishnan, Kalaimagal; Yasin, Norizan Mohd; Selvaraj, K.R.; Periyasamy, Jeyarani (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The Malaysian government sees education as one of the important factors in the country’s advancement. In order to achieve this, Malaysia needs to have an up-to-date technology such as Social Media Technologies (SMTs) to support the learning system in Higher learning institutions (HLIs). There is a great argument that 21st Century students learn differently. SMTs help to form a student-centered environments among the digital generation. It bridges a gap in knowledge in relation between SMTs and its impact in HLIs. Mobile learning and SMTs deliver the ability to communicate with academicians and students. HLIs should take this opportunity to connect SMTs to design a modern educational setting that will advance their learning experiences. It shows that SMTs have a great value for academic associated, particularly as a teaching and learning tool. HLIs and students have identified numerous challenges related to the adoption process. This study reviews and evaluates the SMTs related research articles published in academic journals between the year 2010 to 2018, mainly in HLIs fields. It identifies the impacts of SMTs on both students and academicianss in HLIs and associate how SMTs can be effectively connected to Mobile learning to support and enhance the students’ learning in Malaysia. © 2019, Blue Eyes Intelligence Engineering and Sciences Publication. All rights reserved.